Collection development of non print materials in Filipino Chinese schools in Metro Manila - Singian, Ma. Alma Navarro; Aguirre, Vyva Victoria M.; Lapuz, Elvira B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2010)
Collection development of non-print materials is important today because of the rapid changes in technology. In developing library collection, the school must have a written collection development policy. Developing and managing materials for the Instructional Materials Center have assumed more importance in recent years. For school libraries, collections must serve the academic programs of its community. Likewise, collection is built to support the instructional programs of the schools, thus, only that which can strengthen its program must be made available.
In this research, qualitative research was applied as the researcher would be examining non-print collection development among selected Filipino-Chinese schools. Since there are only few Filipino-Chinese schools, random sampling was not applicable, hence, quantitative measures cannot be utilized. The survey questionnaires were administered school administrators, faculty, librarians and students in High school Department in four Filipino-Chinese Schools in Metro Mania, namely, Jubilee Christian Academy, Makati Hope Christian School, Philippine Cultural College and Xavier School.
The study intended to find out the effectiveness of collection development policies in Filipino-Chinese schools. It showed in this research also that among the four schools that responded only one claimed that they have CDP and it is being used for the development of its collection. Findings of the study showed what kind of materials they acquire, how the Filipino-Chinese schools develop their non-print materials and the identification of the need for the availability, usability and effectiveness and the level of user's satisfaction of the non-print materials. The importance of non-print materials was also established to address the present day trends and issues.
It is therefore recommended that schools develop and write down collection policy to serve and satisfy the needs of the library users.
Vita.
Special Problem (Master of Library and Information Science)
Keywords: School libraries (High school) -- Collection development -- Philippines -- Manila Metropolitan Area; Nonbook materials -- Philippines -- Manila Metropolitan Area; Schools, Chinese -- Philippines -- Manila Metropolitan Area